Polyhydroxypregnane glycosides from Dregea volubilis - Tuan Phuong, Phan; Anh, Phan Thi Lan; Nhiem, Nguyen Xuan; Thuy, Nguyen Thi Kim; Van Kiem, Phan (Vietnam Journal of Science and Technology, 2020)
Four known polyhydroxypregnane glycosides, dregeoside Da1 (1), volubiloside A (2), drevoluoside N (3), and volubiloside C (4) were isolated from the methanol extract of the leaves of Dregea volubilis. Their structures were elucidated by 1D-, 2D-NMR, spectra and comparing with those reported in the literature.